From Sacred Relic to Tourist Attraction: The Development of Kiskendo Cave in Kulon Progo Regency, 1964–2005 - Muhammad Fikriansyah Aziz; Siska Nurazizah Lestari; Anggar Kaswati (Warisan: Journal of History and Cultural Heritage, 2024)
This study explores the historical evolution of Kiskendo Cave in Kulon Progo Regency from 1964 to 2005, focusing on the role of the Tourism Awareness Group in managing and preserving the site. Employing a historical research methodology, the study follows five key stages: (1) topic selection; (2) heuristics; (3) source criticism; (4) interpretation; and (5) historiography. The findings indicate that between 1974 and 1978, the Level I Government of the Special Region of Yogyakarta acquired approximately 5 hectares of land surrounding the cave. Subsequently, on July 26, 1987, Sri Sultan Hamengkubuwono IX officially inaugurated Kiskendo Cave as a public tourist attraction. Further developments took place in 2005 when the provincial government delegated the cave’s management to the Kulon Progo Tourism Office, aiming to enhance regional revenue through tourism. The study underscores the transformation of Kiskendo Cave from a sacred site into a significant tourism destination, highlighting the crucial role of local governance and community involvement in its preservation. By examining this transformation, the research contributes to a broader understanding of historical site management and sustainable tourism development in Indonesia.